Coercivity enhancement of hexagonal ferrites - Jacobo, Silvia Elena (2013)
Hexagonal ferrites have been widely used as permanent magnets since their discovery in the 1950s. In spite of their relatively modest magnetic properties, ferrite magnets still show the best performance-to-cost ratio and different investigators are trying to improve their magnetic capabilities by using different synthesis methods and compositions. Different scientific investigations and techniques (Mössbauer spectrometry, X-ray diffraction, and magnetic measurements) have allowed to optimize the permanent magnet properties of rare earth substituted hexagonal ferrite magnets such as La-Co and Nd-Co Sr and Ba ferrites. However, the solubility of rare earth ions in M-type hexaferrite is very low and their introduction leads to the formation of secondary phases, which must be avoided in order to obtain permanent magnets with optimal properties. We report results on enhanced coercivity of hexagonal Sr ferrites with Nd-Co substitution synthesized by the self-combustion method and calcination at 1100°C for two hours. The synthesis of this kind of ferrite is performed with a deficient, non-stoichiometric iron content (ratio Fe/ Sr1xRx of 10 and 11 instead of 12) in order to explore the presence of secondary phases. Comparison with samples of the same composition and stoichiometric formulation is made. Samples with lower iron content show the highest saturation magnetization, remanence and/or coercivity, indicating that the best results for applications of this ferrite will be obtained with an iron deficiency in the stoichiometric formulation. Nd substitution enhances the ferrite anisotropy and coercivity with respect to the unsubstituted sample.